O processo de ensino-aprendizagem da língua portuguesa : representações sociais de professoras dos anos iniciais do ensino fundamental - Lima, Rosely Ribeiro (2013)
This research aims to understand the social representations of teachers who work from 1st to 5th grade of elementary school in the public system in the municipal urban area of the city of Jatai, State of Goias, about the process of teaching and learning Portuguese. The question that guided this project was: What are the social representations of teachers about the process of teaching and learning Portuguese? Over the nearly three years we did 156 different contact to achieve such indications of social representations. First we realized a pilot study to know the notional universe. In this phase we talked with six teachers Trough interview. After that we conducted the second phase of collecting material data, in this moment we talked with 100 teachers. We used the technique of free association to identify the structure of social representation. Finally in the third phase we collected texts in the field, interviewing 50 teachers. Some professionals gave more than one interview to us. In this moment we had the opportunity to know the representational subject in contextualized format. The words from the teachers were recorded, written and organized with the help of two software. The software EVOC was used to process the material collected with the technique of free evocation and the software ALCESTE was used to process the texts collected in the moment of the interview. Guided by the fundamentals of Social representation theory , theory of the central core and knowledge in the formation area of teachers and the language we had done our comprehension considering the specificity in each organization where the material were collected. From the result we understood that the social representation of teachers about the teaching and learning process of Portuguese language in the school is formed by elements anchored in the social valorization for the specific use of language in the society and by elements targeted in the frequent practice of reading in the classroom. The teachers showed that the main principle to be drawn within the process of teaching and learning the Portuguese language is the promotion of reading practice, therefore the reading practice guides to other practice such as writing texts that follow the spelling rules of Portuguese language. The teachers receive many historic and social influences to do their job, like; laws, rules, social values that the family and the society bring due to the way that teaching and learning Portuguese language must happen in the schools and also they have influence by values that give importance to the correct use of Portuguese language in the society. The social enrollment by the teachers are located within a big web of elements that interrelate and make many effects, then start ways of being and do in the teachers occupation. Inside the web of elements, the professional teachers build their job. Then the main effect of this social enrollment in the multiple space of demanding that they know all the elements inside the educational practice and they learn how to deal in singular plane of each individual and also in the plural plans of relationship among all the elements.